2021
DOI: 10.1186/s12877-021-02325-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a programable body-worn digital hearing aid for older adults in a developing country: a randomized controlled trial with a cross-over design

Abstract: Background Hearing aids are important assistive devices for hearing rehabilitation. However, the cost of commonly available commercial hearing aids is often higher than the average monthly income of individuals in some developing countries. Therefore, there is a great need to locally produce cheaper, but still effective, hearing aids. The Thai-produced P02 hearing aid was designed to meet this requirement. Objective To compare the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…ARHL, one of the most common sensory disorders, has become the main cause of communication deficits in elderly individuals and seriously affects their quality of life [19]. A growing number of studies have revealed that epigenetic mechanisms, including DNA methylation, histone modification, and noncoding RNA activities, are involved in the development of ARHL [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…ARHL, one of the most common sensory disorders, has become the main cause of communication deficits in elderly individuals and seriously affects their quality of life [19]. A growing number of studies have revealed that epigenetic mechanisms, including DNA methylation, histone modification, and noncoding RNA activities, are involved in the development of ARHL [20,21].…”
Section: Discussionmentioning
confidence: 99%